Study on Program Production of Liputan Cilik Daai Tv - Mariana Mariana; Heribertus Sunu Budihardjo (Humaniora, 2016)
Research goal of this study was to know the program production process of Liputan Cilik DAAI TV in Jakarta. Method used in this study was a qualitative method with analysis participatory observation and in-depth interviews with the crew involved in this program. Result of this study finds that there are three stages of the program production process, they are pre production, production and post-production programs, and processes of SWOT analysis (Strength, Weakness, Opportuniy, Threats). This program has done production in accordance with the SOP (standard operation procedure) although it is aired on television non-commercial. This program does not only provide the entertainment, but also contains the elements education.